Genetic parameters and correlations for seed yield and morphological characters in Indian mustard [Brassica juncea (L.) Czern. and Coss.]: GENETIC PARAMETERS AND CORRELATIONS FOR SEED YIELD IN INDIAN MUSTARD - C P MEENA; J S CHAUHAN; M SINGH; K H SINGH; S S RATHORE; M L MEENA (Journal of Oilseeds Research, 2014)
The present investigation was carried out during rabi season of 2007-08 with 60 germplasm accessions of Indian mustard from China, India and Australia and 5 check varieties. The material was grown in an augmented block design to assess heritability, genetic advance for seed yield and other morphological characters and their inter se relationships. Significant mean sum of squares indicated genotypic differences for all the characters investigated except protein content. Estimates of heritability and genetic advance were high for secondary branches/plant, siliqua length, 1000-seed weight, seed yield/plant and harvest index indicating dominant role of additive gene action in their inheritance. Thus, selection would be effective for their improvement in early segregating generations. Seed yield/plant had significant and positive correlations with secondary branches/plant, main shoot length and siliquae on main shoot. The genetic correlations of seed yield with these characters were also positive and of moderate to high strength suggesting that for yield enhancement in Indian mustard greater emphasis in the selection programme should be laid on these component characters.